Mendelian Randomization Analysis of the Causal Relationship Between Micronutrients and Childhood Asthma - Zhimei Liu (5947499) (2025)
Existing research have suggested a significant association between micronutrients and childhood asthma, but the specific causal relationship between micronutrients and childhood asthma remains unclear. Therefore, we aimed to assess the causal relationship between micronutrients and childhood asthma using Mendelian randomization methods. We conducted two-sample Mendelian randomization analyses and multivariable Mendelian randomization analyses using summary statistics from genome-wide association studies (GWAS) of micronutrients (Copper, Calcium, Carotene, Folate, Iron, Magnesium, Potassium, Selenium, Vitamin A, Vitamin B12, Vitamin B6, Vitamin C, Vitamin D, Vitamin E, and Zinc) and childhood asthma among European individuals from the Open GWAS and FinnGen databases. Five Mendelian randomization methods—Inverse Variance Weighted (IVW), Weighted Median, MR-Egger, Simple Mode, and Weighted Mode—were employed to investigate the causal relationship between micronutrients and childhood asthma. The IVW method revealed a significant inverse association between zinc and the risk of childhood asthma (OR: 0.002, 95% CI: 0.000-0.153, p = 0.005). Copper (OR: 0.998, 95% CI: 0.947-1.052, p = 0.951), Selenium (OR: 0.967, 95% CI: 0.866-1.079, p = 0.544), Folate (OR: 0.885, 95% CI: 0.603-1.300, p = 0.534), Carotene (OR: 0.849, 95% CI: 0.594-1.215, p = 0.371), Potassium (OR: 1.262, 95% CI: 0.836-1.905, p = 0.268), Vitamin D (OR: 1.237, 95% CI: 0.791-1.934, p = 0.352), Vitamin C (OR: 1.154, 95% CI: 0.759-1.756, p = 0.503), Vitamin B12 (OR: 1.177, 95% CI: 0.754-1.839, p = 0.473), Iron (OR: 0.873, 95% CI: 0.552-1.383, p = 0.563), Vitamin E (OR: 1.082, 95% CI: 0.768-1.524, p = 0.651), Magnesium (OR: 1.190, 95% CI: 0.828-1.712, p = 0.347), Vitamin B6 (OR: 0.928, 95% CI: 0.592-1.456, p = 0.746), Calcium (OR: 1.255, 95% CI: 0.840-1.876, p = 0.268), and Vitamin A (OR: 3.928, 95% CI: 0.001-15166.57, p = 0.745) had no significant causal associations with childhood asthma. The multivariable Mendelian randomization analysis for zinc, Vitamin A, and Vitamin C indicated that zinc is a significant protective factor against childhood asthma (OR: 0.001, 95% CI: 0.000-0.165, p = 0.007). In contrast, Vitamin A and Vitamin C did not show significant causal relationships with childhood asthma when controlling for zinc levels. Our study confirms the specific causal relationships between micronutrients and childhood asthma using Mendelian randomization methods.